Current and future therapeutic approaches to the congenital myopathies. (April 2017) - Jungbluth, Heinz; Ochala, Julien; Treves, Susan; Gautel, Mathias
Abstract: The congenital myopathies – including Central Core Disease (CCD), Multi-minicore Disease (MmD), Centronuclear Myopathy (CNM), Nemaline Myopathy (NM) and Congenital Fibre Type Disproportion (CFTD) – are a genetically heterogeneous group of early-onset neuromuscular conditions characterized by distinct histopathological features, and associated with a substantial individual and societal disease burden. Appropriate supportive management has substantially improved patient morbidity and mortality but there is currently no cure. Recent years have seen an exponential increase in the genetic and molecular understanding of these conditions, leading to the identification of underlying defects in proteins involved in calcium homeostasis and excitation-contraction coupling, thick/thin filament assembly and function, redox regulation, membrane trafficking and/or autophagic pathways. Based on these findings, specific therapies are currently being developed, or are already approaching the clinical trial stage. Despite undeniable progress, therapy development faces considerable challenges, considering the rarity and diversity of specific conditions, and the size and complexity of some of the genes and proteins involved. The present review will summarize the key genetic, histopathological and clinical features of specific congenital myopathies, and outline therapies already available or currently being developed in the context of known pathogenic mechanisms. The relevance of newly discovered molecular mechanisms and novel gene editing strategies for future therapy development will be discussed.